6(t-5)=5t

Simple and best practice solution for 6(t-5)=5t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(t-5)=5t equation:


Simplifying
6(t + -5) = 5t

Reorder the terms:
6(-5 + t) = 5t
(-5 * 6 + t * 6) = 5t
(-30 + 6t) = 5t

Solving
-30 + 6t = 5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5t' to each side of the equation.
-30 + 6t + -5t = 5t + -5t

Combine like terms: 6t + -5t = 1t
-30 + 1t = 5t + -5t

Combine like terms: 5t + -5t = 0
-30 + 1t = 0

Add '30' to each side of the equation.
-30 + 30 + 1t = 0 + 30

Combine like terms: -30 + 30 = 0
0 + 1t = 0 + 30
1t = 0 + 30

Combine like terms: 0 + 30 = 30
1t = 30

Divide each side by '1'.
t = 30

Simplifying
t = 30

See similar equations:

| 6y-11=49 | | 12y+6=22 | | 12+6=22 | | 6+4Y=2X | | h=1200-16t | | (4-3w)-(2-5w)= | | 2(r-2)=-3(4+2r) | | 50+6b=86 | | 7x^2+6x=17x-5x^2 | | (x+5)+2x=26 | | 8h-29=43 | | 6h-12=2h+36 | | -c=c+10 | | x^6=81 | | 10-3b=-10-8b | | 6-4(3x-3)=6 | | -3.5=9.4k+3(-3k-1.7) | | 6(x+5)=7.5 | | 5y-9+y+29=8y+20-4y | | -9-2p=-p | | 5x-9+x+29=8x+20-4x | | 4a^2+15a-25=0 | | 325.8+(-21.13)=114.5 | | 2(x-6)=8(x+3) | | 3(8)-4=12 | | 2(x-8)=8(x+3) | | 2k+9=-7k | | 3x+15=3x-10 | | 2ln(x+1)-1=0 | | -8x-7x=-120 | | -10y-6=-9y | | 7x-12x=-5 |

Equations solver categories